The gag in 9Gag humor on the internet as portrayed in 9Gag videos - Castro, Kim Ysabel T. 1992- (2013)
"This study looked into how sense of humor was manifested in the Internet as portrayed in 9GAG videos. The method that was employed to analyze the data was content and textual analysis. The videos were analyzed based on the theories on which the humorous texts are grounded, the elements seen in the videos and the technique of humor used. The humor theories which were used were: Superiority, Incongruity, Ambivalence, and Relief Theory. It has been found that the most dominant humor theory which the videos were grounded was the Incongruity theory. The results also showed that the most dominant element and technique used for humor were target and sexual allusion respectively. An additional category of humor was also seen in the results which was "unusual things or events." The date showed that the content of 9GAG is not purely on things that people find funny but also of things and circumstances that are unusual and interesting. The findings of the study revealed that the humor technique mostly used in the videos was that of Sexual Allusion and the theme that emerged as most dominant was "Women as Sex Objects". This has been an issue in the past decades and continues until today, even in the Internet."